The Design of a Rubric to Evaluate Laboratory Reports in Astronomy: Academic Literacy in the Disciplines - María Cristina Arancibia Aguilera (Universidad Nacional de Colombia, 2014)
A rubric was developed to evaluate laboratory reports written by undergraduate students of astronomy and astrophysics from Universidad Católica de Chile. The process of elaboration, peer validation, and application of the rubric to the evaluation of written tasks extended from August 2011 to August 2012. The instrument proved to be effective as an assessment tool that guides teachers towards the fundamental criteria that must be considered when evaluating their students' writing. Moreover, the instrument provides useful guidelines to direct students' attention towards the critical components of the laboratory report genre.